Influence of supervisees' working alliance on supervision outcomes: a study in Malaysia context - Ghazali, Nor Mazlina; Wan Jaafar, Wan Marzuki; Ahmad Tarmizi, Rohani; Mohd Noah, Sidek (International Association of Computer Science and Information Technology Press, 2016)
Supervisory working alliance is an essential element in the supervision process. The experiences of supervisees during dyad or supervision process with their supervisors contribute to the levels of relationships (positive or negative) between supervisors and supervisees in their working alliance. The purposes of the research are to determine the relationships between supervisees’ working alliance and supervision outcomes and to investigate the influence of supervisees’ working alliance on the supervision outcomes. This quantitative study consists of two types of respondents: 1) supervisee (counselor trainee) and 2) supervisor (academic lecturer). A total of 120 supervisees and 18 supervisors participated in the research. This study found that there was a significant relationship between supervisees’ working alliance and supervision outcomes (supervisees’ satisfaction and performance) [F (1, 116) = 49.5, (β = 1.04, p < 0.05), r =. 55 (adjusted R2 =. 293)]. As a conclusion, the supervisees’ working alliance has a unique contribution on the supervision outcomes (supervisees’ satisfaction and performance) among supervisees (counselor trainees) in Malaysia.